Transport and Kinetic Property of the Butyric Acid in Water: A Simulation Study - Priya Dey; Vishal Singh; Hemant Kumar (Chemical Physics Impact)
Microbiota is defined as a class of all microorganisms which includes fungi, protozoa, bacteria and viruses. About 90 % of all microbiota in our body are found in our gut that regulates host immunity. The gut-brain axis is a bidirectional communication system that allows gut microbiota to communicate with the brain and vice versa. Studies suggest that the gut dysbiosis may enhance neurotoxic substances such as short-chain fatty-acids (SCFAs which are acetate, propionate, and butyrate) to the blood circulation and even to the brain through damaged blood brain barrier (BBB) and may cause protein aggregation which are implicated in the pathogenesis of several neurodegenerative diseases like Alzheimer’s disease (AD), Parkinson’s disease (PD), prion disease, motor neuron disease, Huntington’s disease (HD), Amyotrophic lateral sclerosis (ALS). Specifically, butyric acid are the main SCFA product that may impact on gut health. Therefore, this article aims to investigate the transport and kinetic properties such as diffusion coefficient, activation energy and radial distribution function of butyric acid in water at different temperatures through molecular dynamics simulations. The self and binary diffusion coefficient of butyric acid in water obtained from our MD simulation are found to be 0.8699×10−9m2s−1 and 0.8714×10−9m2s−1, respectively at 300 K and the activation energy for self-diffusion coefficient of water estimated from the slope of ln(D) versus 1/T is equal to 16.07 kJ/mol. Our results are in accordance with those obtained from the experimental values. This study offers an alternate approach to researching the diffusion of butyric acid in living organisms. This knowledge contributes to advancements in various fields, including nutrition, gastroenterology, microbiology, and pharmacology.